An evaluation of coastal law enforcement in the municipality of San Jose de Buenavista, Antique - Enriquez, Eustacio Nimrod P. (University of the Philippines in the Visayas, 2002)
A study aimed the effectiveness and efficiency of coastal law enforcement in San jose de Buenavista, Antique. A survey questionnaire and interview guide questions was used for personal interview with each of the respondents from the fisherfolks, commercial fishing boat operators and law enforcers. The study revealed that there is a very low level of awareness on the Municipal Fisheries Code of San Jose as well as on other common coastal laws. The most common violations were encroachment on municipal waters by commercial fishing boats aand pollution from agricultural runoffs and households. Furthermore, violations are committed for profit, also due to poverty, stubbornness and for convenience. The fisherfolks and commercial fishing boat operators recommend that coastal law enforcement approach ust be hard (corrective) by apprehending violators. The law enforcers, on the other hand, recommend soft (preventive) mechanisms such as conducting info drive to increase level of awareness on coastal laws. It is interesting to note that number of the respondents are of the opinion that coastal law enforcement has no effect on fish productivity and bio-diversity. This is based on their knowledge of the water topography of Antique that is very deep and the migratory nature of fishes caught in the province. The fisherfolks and commercial fishing boat operators perceived that the main hindrances to coastal law enforcement are the lack of patrol boats and corruption on the part of the law enforcers. However, the law enforcers perceived that it is the lack of patrol boats, communications equipment, personnel, and political will that hinders law enforcement. The fisherfolks, commercial fishing boat operators and law enforcers gave an average perceived rating of 2.5 (below passing), 3.0 (passing, and 3.4 respectively for the effectiveness and efficiency of coastal law enforcement in San Jose. The awareness, understanding and appreciation of the coastal laws and the coastal environment may be increased through a pro-active information, education and communication (IEC) campaigns for both government and citizenry. There must be an active initiative and leadership by the Local Government Unit (LGU) on Coastal Resource Management (CRM). Furthermore, there must be an inter-agency cooperation for a multi-role enforcement.